Teacher performance analysis using Smart PLS - Ratih Pratiwi; Anuar Sanusi; MS Said Hasibuan (Prosiding International conference on Information Technology and Business (ICITB), 2022)
This study aims to conduct a study of improving teacher performance through Organizational Citizenship Behavior, Communication Organizational Culture and Leadership Style at PKLK Growing Hope Bandar Lampung, Lampung. The study was conducted on 4 variables, namely Organizational Citizenship Behavior, Communication Organizational Culture and Leadership Style to improve teacher performance at PKLK Growing Hope Bandar Lampung, Lampung. Model analysis using Structural Equation Modeling. as if the analytical tool used is Partial Least Square (PLS) with Smart PLS 3.0 software starting from the measurement model (outer model), model structure (inner model), and hypothesis testing. The results of the study indicate that there is a significant influence of Organizational Citizenship Behavior on Teacher Performance, proving that there is a significant influence of Organizational Culture on Teacher Performance, there is a significant influence of Communication on Teacher Performance. Simultaneously hypothesis testing also proves to show that there is a significant influence of Leadership Style on Teacher Performance. There is a positive and significant correlation between the variables of Organizational Citizenship Behavior, Communication Organizational Culture and Leadership Style with the improvement of teacher performance at PKLK Growing Hope Bandar Lampung, Lampung. The results of the R Square measurement have a value of 95% while 5% are outside of the variables studied. This shows that there are several other variables that can be investigated to complete this research.Keywords— Organizational Culture, Communication, and Leadership Style